Інґеборґ Бахман та австрійська столиця: «Маліна» як віденський роман - Isapchuk, Yulia (Київ: КНЛУ, 2020)
The report analyzes the novel by the prominent Austrian writer I. Bachmann «Malina» (1971), which is part of the author’s cycle «Death Styles» («Todesarten»). The role of the autobiographical components of the text is emphasized: characteristics of origin, appearance, job of the female narrator. It clarifies the contradictory image of the Austrian capital using the space of remembrance and places of memory. Attention is drawn to the post-war atmosphere of Vienna, which adds its modifications to the image of the clichéd cultural metropolis. The topography of the city is studied. The reader can easily imagine a walk through the labyrinth of the central Viennese streets, pointing to its most important places (Stadtpark, Belvedere Palace, Squares Heumarkt and Am Hof) and special locations of food infrastructure. They also reveal the relationship’s patterns of the novel’s characters. The strong emphatic connection between the narrator and the Austrian capital is shown on the basis of the relations with the main male character Ivan and the locus of the Ungargasse. The route to the home of the female narrator and Malina (house № 6) and Ivan (house № 9), located on street Ungargasse, is described in detail. It is associated with a utopian chronotope in the inset legend «The Mysteries of the Princess of Kagran» in the novel. Due to the locus Ungargasse, the city became a topos of happiness because of love to Ivan for a short period, ending with another invisible «death style» (the female narrator disappears into a crack in the wall). I. Bachmann also mentions several times another street (Beatrixgasse 26). This is a real address, where the writer and the narrator in the text originally lived. This place of memory evokes a sense of security and reminds positive moments in the author’s Viennese life. In «Malina» as an overture to the «Death Styles», the Austrian capital represents in the best way the interconnectedness of the characters from this cycle. I. Bachmann refers to the Viennese «universal prostitution», when the couples suddenly changed their partners, demonstrating the circulation of human destinies in society. The author makes evident the concept of society as the biggest scene of murders, which runs through all her work. The ironic-satirical image of the Austrian metropolis is shown by the depicting of the beau monde’s everyday life.Two families reflect post-war Vienna as changing and actively adopting the new trends (American way of life). It can be associated with globalization in the modern world. Opposite to them, we observe a noble couple of Altenwyls, who venerates the traditions of the good old Austria. The choice of a figure with such a name emphasizes the intertextual connection with Austrian Modern literature and the atmosphere of the pre-war Vienna (H. von Hofmannsthal’s comedy «Der Schwierige», 1922). As a result, our research determines the Austrian capital according to the topographical, autobiographical, cultural and historical indicators, using the places of memory of I. Bachmann. That’s why we propose considering «Malina» as a Viennese novel based on the spatial communication of an individual with the city.
Ingeborg Bachmann and Austrian metropolis:„Malina” as a Viennese novel
Keywords: I. Bachmann; Malina; Viennese novel; topography; city; metropolis / capital; spatial communication